IMPLIKASI OVER KAPASITAS DI RUMAH TAHANAN NEGARA KELAS II A PONTIANAK TERHADAP GANGGUAN KEMANAN DAN KETERTIBAN - NIM. A1012211177, ANGGA SETYA PAMBUDI (Fakultas Hukum Universitas Tanjungpura, 2025)
This research analyzes the implications arising from the increase in the number of correctional inmates which is not comparable to the housing standards that apply in the Decree of The Minister of Law and Human Rights Number M.01.PL.01.01. 2003 concerning Building Patterns for Correctional Technical Implementation Units. With the theme